A low CO2-responsive mutant of Setaria viridis reveals that reduced carbonic anhydrase limits C-4 photosynthesis - Chatterjee, Jolly; Coe, Robert A.; Acebron, Kelvin; Thakur, Vivek; Yennamalli, Ragothaman M.; Danila, Florence; Lin, Hsiang-Chun; Balahadia, Christian Paolo; Bagunu, Efren; Padhma, Preiya P O.S.; Bala, Soumi; Yin, Xiaojia; et al. (Oxford University Press, 2021)
In C4 species, β-carbonic anhydrase (CA), localized to the cytosol of the mesophyll cells, accelerates the interconversion of CO2 to HCO3–, the substrate used by phosphoenolpyruvate carboxylase (PEPC) in the first step of C4 photosynthesis. Here we describe the identification and characterization of low CO2-responsive mutant 1 (lcr1) isolated from an N-nitroso-N-methylurea- (NMU) treated Setaria viridis mutant population. Forward genetic investigation revealed that the mutated gene Sevir.5G247800 of lcr1 possessed a single nucleotide transition from cytosine to thymine in a β-CA gene causing an amino acid change from leucine to phenylalanine. This resulted in severe reduction in growth and photosynthesis in the mutant. Both the CO2 compensation point and carbon isotope discrimination values of the mutant were significantly increased. Growth of the mutants was stunted when grown under ambient pCO2 but recovered at elevated pCO2. Further bioinformatics analyses revealed that the mutation has led to functional changes in one of the conserved residues of the protein, situated near the catalytic site. CA transcript accumulation in the mutant was 80% lower, CA protein accumulation 30% lower, and CA activity ~98% lower compared with the wild type. Changes in the abundance of other primary C4 pathway enzymes were observed; accumulation of PEPC protein was significantly increased and accumulation of malate dehydrogenase and malic enzyme decreased. The reduction of CA protein activity and abundance in lcr1 restricts the supply of bicarbonate to PEPC, limiting C4 photosynthesis and growth. This study establishes Sevir.5G247800 as the major CA allele in Setaria for C4 photosynthesis and provides important insights into the function of CA in C4 photosynthesis that would be required to generate a rice plant with a functional C4 biochemical pathway.